Recyclable Heterogeneous Copper(II)-Catalyzed Oxidative Cyclization of 2-Pyridine Ketone Hydrazones Towards [1,2,3]Triazolo[1,5-a]pyridines - Jiang, Gan; Lin, Yang; Cai, Mingzhong; Zhao, Hong (Synthesis, 2019)
The heterogeneous copper(II)-catalyzed oxidative cyclization of 2-pyridine ketone hydrazones was achieved in ethyl acetate at room temperature in the presence of an MCM-41-anchored bidentate 2-aminoethylamino copper(II) catalyst [MCM-41-2N-Cu(OAc)2], in the presence of air as the oxidant, yielding a wide variety of [1,2,3]triazolo[1,5-a]pyridines in mostly good to high yields. The present method was also applied to the direct one-pot synthesis of [1,2,3]triazolo[1,5-a]pyridines from 2-acylpyridine derivatives and hydrazine monohydrate. Importantly, this supported copper(II) catalyst could be conveniently obtained via a simple procedure from easily available and inexpensive reagents, recovered by filtration of the reaction mixture, and reused at least seven times without a significant loss of catalytic activity.
Keywords: copper catalysis; [1,2,3]triazolo[1,5-a]pyridines; oxidative cyclization; heterogeneous catalysis; N–N coupling